Lossy Mode Resonance Sensors Based on Planar Waveguides: Theoretical and Experimental Comparison - Edvins Letko; Arturs Bundulis; Gatis Mozolevskis (IEEE Photonics Journal)
Lossy mode resonance (LMR) has garnered significant attention in sensor applications. LMR was primarily explored in fiber-based systems, however, there has been a recent upsurge in its application within planar waveguides. This article compares the LMR phenomenon in planar waveguides with the most employed coatings in the field, specifically SnO2, TiO2, and ITO. Additionally, the experimental findings are compared with simulations conducted using the finite element method (FEM) within the COMSOL Multiphysics environment. The novelty of this research lies in the integration of both experimental results and theoretical calculations, utilizing strong FEM simulation tools, in a single study.